Susceptibility of Poultry Red Mites to Entomopathogens - Kaoud, Hussein A. (International Journal of Poultry Science, 2010)
The killing efficacy of the entomopathogenic fungi Beauveria bassiana and Trichoderma album as well as the bacteria Bacillus nigateria israelensis against the poultry red mite, Dermanyssus gallinae De Geer, 1778 were experimentally evaluated. In spite of Dermanyssus gallinae is a major pest in the poultry production, no information is available on the susceptibility of these mite to entomopathogens. Therefore, infection experiments with two fungi and one bacterial species were carried out in the laboratory. Beauveria bassiana and Trichoderma album were tested in assays in which the mites were exposed to high doses of conidia. Beauveria bassiana and Trichoderma album caused high mortalities within the first 5 and 10 days of exposure as well as the bacteria Bacillus nigateria israelensi. Trichoderma album and Bacillus nigateria israelensi proved to be fatal against the poultry red mite D. gallinae, to our knowledge, this is the first record. Trichoderma album and Beauveria bassiana mixture in built-up litter were highly fatal to poultry red mite.